PERAN HARGA DAN PENAWARAN CASHBACK TERHADAP KEPUTUSAN PEMBELIAN GO-FOOD DENGAN MENGGUNAKAN PEMBAYARAN DIGITAL GOPAY - Dewi Sri Woelandari Pantjolo Giningroem; Novita W Setyawati; Supriyanto Supriyanto (Journal of Management Small and Medium Enterprises (SMEs), 2022)
This study aims to explore the role of price and cashback offer on Go-Food purchase decision by using Gopay digital payment feature found in Gojek application. The type of research is explanatory research with a quantitative approach and use survey methods in data collection. This study involves 100 respondents using the Go-Food application. Data analysis used Multiple Linear Regression Analysis, data quality test, classical assumption test, and hypothesis testing with using SPSS statistical software version 24. The results of this study found that partially the price variable does not have significant influence on Go-Food purchase decision using Gopay digital payment. Meanwhile the cashback offer variable has significant influence on Go-Food purchase decision in using Gopay digital payment. However, both the price variable and the cashback offer have a significant effect simultaneously on Go-Food purchase decision using Gopay digital payment. So it can be concluded that the cashbach offer is an effective marketing strategy to attract consumers in deciding to purchase Go-Food using Gopay digital payment. For future research, it is better for the price variable to be studied in the selection of indicators. In addition, it is better to add a mediating or moderating variable that can bridge the research gap, or add other variables such as product rating, product quality, and others, so it can be improve Go-Food consumers purchase decision using Gopay digital payment. Keywords: Consumer Purchase Decision, Gopay Digital Payment, Cashback Offer, Price